Can Workers in Low-End Occupations Climb the Job Ladder?. Issue 2 (May 2019) - Gabe, Todd; Abel, Jaison R.; Florida, Richard
There is growing concern over rising economic inequality, the decline of the middle class, and a polarization of the U.S. workforce. This study examines the extent to which workers in the United States transition from low-end to higher-quality occupations, and explores the factors associated with such a move up the job ladder. Using data covering the expansion following the Great Recession (2011-2017) and focusing on short-term (i.e., less than 1 year) labor market transitions, the authors find that just slightly more than 5% of workers in low-end occupations moved into a higher-quality occupation. Instead, around 70% of workers in low-end occupations stayed in the same occupation, 11% exited the labor force, 7% became unemployed, and 6% switched to a different low-end occupation. Study results point to the importance of educational attainment in helping workers successfully climb the job ladder.